2018
DOI: 10.1515/sjpain-2018-0304
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal pain in multiple body sites and work ability in the general working population: cross-sectional study among 10,000 wage earners

Abstract: Abstract Background and aims Musculoskeletal pain may negatively affect work ability, especially when work demands are high and/or physical capacity of the worker is low. This study investigated the association between intensity of musculoskeletal pain in multiple body regions and work ability among young and old workers with sedentary and physical demanding jobs. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 32 publications
5
42
0
2
Order By: Relevance
“…The present cross-sectional study employ self-reported data on work ability and physical work demands from the 2010 round of the Danish Work Environment Cohort Study (DWECS). DWECS is a comprehensive questionnaire survey assessing work environment and health among the general working population residing in Denmark [4,19]. Specific questions used in this study are specified below.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The present cross-sectional study employ self-reported data on work ability and physical work demands from the 2010 round of the Danish Work Environment Cohort Study (DWECS). DWECS is a comprehensive questionnaire survey assessing work environment and health among the general working population residing in Denmark [4,19]. Specific questions used in this study are specified below.…”
Section: Methodsmentioning
confidence: 99%
“…Those not responding received one or more reminders. A total of 53% (10,605 workers) responded to the questionnaire [4,19]. The present study included only physical workers (n = 5377), identified by the following question: 'How will you describe your physical activity level in your main profession?'.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…[22][23][24][25] However, this is especially important in professionally active workers, as musculoskeletal pain can be the factor that reduces the ability and capacity to work. 26,27 It should also be noted that the prevalence of musculoskeletal disorders (MSD)(including the joints, muscles, ligaments, nerves, tendons, and structures that support limbs, neck and back) increases with age. 28 Therefore, special attention should be paid to the relation between physical activity and musculoskeletal symptoms among middle-aged and older adults who are still professionally active.…”
Section: Introductionmentioning
confidence: 99%